2009
DOI: 10.1681/asn.2008070798
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Microvesicles Protect Against Acute Tubular Injury

Abstract: Administration of mesenchymal stem cells (MSCs) improves the recovery from acute kidney injury (AKI).The mechanism may involve paracrine factors promoting proliferation of surviving intrinsic epithelial cells, but these factors remain unknown. In the current study, we found that microvesicles derived from human bone marrow MSCs stimulated proliferation in vitro and conferred resistance of tubular epithelial cells to apoptosis. The biologic action of microvesicles required their CD44-and ␤1-integrin-dependent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,173
1
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,170 publications
(1,240 citation statements)
references
References 42 publications
36
1,173
1
9
Order By: Relevance
“…65 MSCs express high levels of genes essential to the regulation of haemopoietic stem cells, 66 stimulate proliferation of endogenous cardiac progenitor cells during experimental myocardial infarction, 67 and possibly increase the number of lung progenitor cells in response to injury. 65 Finally, MSCs seem able to aff ect tissue repair through the delivery of extracellular vesicles 68,69 and direct mitochondrial transfer. 70 Although a detailed exploration of this scientifi c literature is beyond the scope of this review, table 5 shows a brief overview of several representative studies.…”
Section: Alternative Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…65 MSCs express high levels of genes essential to the regulation of haemopoietic stem cells, 66 stimulate proliferation of endogenous cardiac progenitor cells during experimental myocardial infarction, 67 and possibly increase the number of lung progenitor cells in response to injury. 65 Finally, MSCs seem able to aff ect tissue repair through the delivery of extracellular vesicles 68,69 and direct mitochondrial transfer. 70 Although a detailed exploration of this scientifi c literature is beyond the scope of this review, table 5 shows a brief overview of several representative studies.…”
Section: Alternative Pathwaysmentioning
confidence: 99%
“…Bruno et al 68,71 Microvesicles derived from human MSCs had protective eff ects in both in-vitro and in-vivo acute kidney injury models Lee et al 72 Intravenous administration of MSC-derived exosomes decreased the infl ux of infl ammatory mediators and inhibited vascular remodelling and pulmonary hypertension in a murine model of hypoxia-induced pulmonary hypertension…”
Section: Summary Extracellular Vesiclesmentioning
confidence: 99%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%
“…[34][35][36] Interestingly, Bruno's group confirmed that microvesicles derived from MSCs could protect against acute renal tubular injury via cell-tocell communication. 37,38 Exosomes/microvesicles contain mRNAs, microRNAs, and proteins, and our previous work indicated that hucMSCs and hucMSC-Ex can alleviate CCl 4 -inducued liver injury as that observed in hucMSCs, 10,39 suggesting that MSC-derived exosomes may be critical to reversing liver injury. Thus, we sought to understand the route, dose, and mechanism for the hepatoprotective role of hucMSC-Ex.…”
Section: Discussionmentioning
confidence: 90%